Examination of the Validity of Environmental Kuznets Curve (EKC) Hypothesis in Nigeria (1960-2014) - Inuwa Dauda, Mohammed; Donga, Manu; Muhammed , Kabiru; Gimba Alhassan, Yerima (Kashere Journal of Humanities, Management and Social Sciences, 2022)
This study examines the validity of Environmental Kuznets Curve (EKC) Hypothesis in Nigeria from 1960 to 2014. The study employs annual time series data on carbon dioxide (CO2) emissions, income, population growth and trade openness from 1960 to 2014. The study uses the robust Autoregressive Distributed Lag (ARDL) bounds testing method to analyze the data. The findings of the study reveals that there is no evidence of existence of long run equilibrium relationship among carbon dioxide (CO2) emissions, income, population growth and trade openness in Nigeria for the period under study. Although in the short run, income per capita, income per capita squared, and income per capita cubed have satisfied the inverted U-shaped of the Environmental Kuznets Curve (EKC) hypothesis, but found statistically not significant in influencing changes in carbon dioxide (CO2) emissions at any conventional level of significance. Similarly, the short run coefficient of population growth (POG) turnout positive as expected, but found statistically not significant at the conventional level of significance. However, the coefficient of trade openness (TRO) differs from a priori expectation, which shows negative and also found statistically significance. The study recommends that further studies should pay attention to the effect of increasing level of urbanization, agricultural activities and fossil fuels in exploring the EKC hypothesis in Nigeria. It also recommended that further studies should capture local environmental pollutants in Nigeria such as deforestations, combustible renewable and waste to determine whether that can make significant difference from the results of previous studies.